Criteria to scrutinize new rights: protecting rights against artificial proliferation - Netto, Luisa (Revista de Investigações Constitucionais, 2021)
Human and fundamental rights are powerful legal means to protect and promote human dignity. On the one hand, the recognition of implicit and new rights appears unavoidable and desirable as history and its evolving circumstances permanently present new challenges to human dignity. On the other hand, an artificial proliferation of rights can weaken rights’ legal and political worth. The rights system cannot expand limitless, hence criteria to test new rights must be construed in the search of adequate parameters to update the system. These criteria should reveal the presence of substantial fundamentality in rights not explicitly or formally enshrined in the constitutional text. The testing path of new rights is conceived as a discursive process which reinforces the mutual relation between rights and democracy.